1981
DOI: 10.1111/j.1365-2133.1981.tb00972.x
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the effect of photo-chemotherapy (PUVA) and UV-B phototherapy in the treatment of psoriasis

Abstract: SUMMARY We have shown that it is possible to produce a satisfactory clinical response with a low UV‐A dosage regime in approximately one‐third of patients with widespread chronic psoriasis. UV‐B phototherapy is as effective initially, but the improvement is not as well maintained as that resulting from photochemotherapy (PUVA). However, in view of the probability that unwanted side effects of PUVA are related to the amount of UV‐A irradiation administered, it would seem appropriate to restrict the use of the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…An emission spectrum in the visible and UV wavelength range was obtained with a spectroradiometer (Spectro-Systems Ltd). The irradiance was measured with a Waldmann PUVA meter as used in dosimetry for the UV-A photochemotherapy of psoriasis (Wolff et al, 1976;Diffey, Challoner & Kay, 1980;Kenicer et al, 1981). This instrument had been calibrated indirectly against a standardised linear thermophile (Rank-Hilger, and was used to determine the total UV-A output of the fluorescent tubes of the sun-bed.…”
Section: Methodsmentioning
confidence: 99%
“…An emission spectrum in the visible and UV wavelength range was obtained with a spectroradiometer (Spectro-Systems Ltd). The irradiance was measured with a Waldmann PUVA meter as used in dosimetry for the UV-A photochemotherapy of psoriasis (Wolff et al, 1976;Diffey, Challoner & Kay, 1980;Kenicer et al, 1981). This instrument had been calibrated indirectly against a standardised linear thermophile (Rank-Hilger, and was used to determine the total UV-A output of the fluorescent tubes of the sun-bed.…”
Section: Methodsmentioning
confidence: 99%
“…UVB phototherapy was found to be effective initially, but the improvement is not as well maintained as that resulting from photochemotherapy (PUVA). In view of the probability that the unwanted side‐effects of PUVA were related to the amount of UVA irradiation administered, however, the use of high UVA doses was restricted to patients who had not responded to an initial low regimen of UVB phototherapy 47 …”
Section: Discussionmentioning
confidence: 99%
“…In view of the probability that the unwanted side-effects of PUVA were related to the amount of UVA irradiation administered, however, the use of high UVA doses was restricted to patients who had not responded to an initial low regimen of UVB phototherapy. 47 Cyclosporine has partially replaced PUVA as a highly effective treatment of psoriasis for over 10 years now. It has been demonstrated that the efficacy and side-effects of cyclosporine in psoriasis, namely hypertension and renal dysfunction, are dose-related, and that an initial dose of 3 mg/kg/day has a better risk/benefit ratio than 5 mg/kg/ day.…”
Section: Discussionmentioning
confidence: 99%
“…But the difference between the spectral composition ( Fig. i) of the two types of tubes is also important (Kenicer et al, 1981). An important difference between the spectral output of the UV-6 and the UV-21 is that the latter lamp emits 11 ^''n of its UV-B in the region between 295 and 300 nm whereas the UV-6 emits no light in this area.…”
Section: Discussionmentioning
confidence: 99%
“…UV-B phototherapy with various radiation sources has attracted increasing interest in the last few years (Tronnier & Heidbiichel, 1976;Holzle, igSo;Adrian et al, 1981;Boer, Schothorst& Suurmond, 1981;Larko, 1982). The results have been reported to be either equal to or only slightly inferior to those obtained with PUVA ( van Weelden, Young & van der Leun, 1980;Kenicer et al, 1981;Parrish, 1981;Vella Briffa et al, 1981;Boer et al, 1983). UV-B therapy has several advantages over PUVA, including the absence of nausea, much less pruritus, no photosensitivity on the day of treatment, no need for contraception, shorter irradiation times, and possibly fewer long-term oncogenic effects, although this last remains to be proved (van Weelden et al, 1980;Larko, 1982).…”
mentioning
confidence: 95%